The Effect of Healthy Living Behaviors, Physical Education Learning Equipment and Body Weight on The Physical Fitness of Junior High School Students - Andriansyah Soamalon Harahap Rian; Susilo; Yasep Setiakarnawijaya; Oman Unju Subandi (Gladi : Jurnal Ilmu Keolahragaan, 2023)
The purpose ofthis research is to determine the influence that arises on healthy living behaviors, learning equipment, and weight loss on the physical fitness of junior high school students post-covid. This research was designed using associative quantitative research methods, with test and non-test techniques then analysis techniques using a path analysis approach. The population in the study was junior high school students totaling 94 students, with sample selection using the volunteer sampling method, which is a sample based on the permission of the principal and parents with the willingness of students to participate in the study. Stages in the study. Based on the results of this study, it can be concluded that (1) There is a significant influence of healthy living behavior on physical fitness by 16.81% (2) There is a significant influence of physical learning equipment on physical fitness by 19.18% (3) There is a significant influence of body weight on physical fitness by 3.68% (4) There is a significant influence of healthy living behavior on body weight by 12.04% (5) There is a significant influence of learning equipment assessment of body weight by 3.65% (6) There was a significant influence of healthy living behavior through body weight on physical fitness of 1.9229 with the calculation of sobel test statistics and (7) There was a significant influence of learning equipment through body weight on referee performance of 2.0047 with sobel test statistical calculation.